Protective effects of ascorbic acid against fluoroquinolone-induced spermatogenic disruption in wistar rats - Abayomi Onaolapo Adeoye; Samuel Oluwatimilehin Apooyin; Bisi Olajumoke Adeoye; Tolulope Ademola Olakojo; Moyinoluwa Julianah Onoja; Adedunsola Adewunmi Obasa; Olawale Olawumi Ola; Akinleye Stephen Akinrinde; John Olumayokun Elijah (Ovozoa: Journal of Animal Reproduction, 2026)
Ciprofloxacin, a widely used fluoroquinolone for the treatment of bacterial infections, has been associated with adverse effects on male reproductive function. This study investigated the protective effects of ascorbic acid on semen quality and testicular histomorphology in male Wistar rats treated with ciprofloxacin. Twenty healthy adults male Wistar rats (100-150 g) were randomly assigned to four groups (n = 5 per group): Group A received distilled water, Group B received ciprofloxacin (135 mg/kg), Group C received ciprofloxacin (135 mg/kg) plus vitamin C (200 mg/kg), and Group D received vitamin C alone (200 mg/kg). After acclimatization, the test substances were administered orally for 14 days. The animals were euthanized 24 hours after the final treatment to evaluate sperm motility, viability, and morphology, as well as testicular histomorphology. Administration of ciprofloxacin alone caused a significant decrease (p <0.05) in sperm motility and viability, accompanied by a marked increase in sperm morphological abnormalities. Testicular histoarchitecture also revealed severe damage, characterized by interstitial oedema, thinning and disorganization of the germinal epithelium, vacuolation of spermatogenic cells, and the absence of mature spermatozoa within the seminiferous tubules. Co-administration of ascorbic acid significantly ameliorated these toxic effects, resulting in reduced sperm abnormalities, improved sperm parameters, and restoration of normal testicular histoarchitecture with active spermatogenesis. In addition, vitamin C alone significantly improved normal sperm morphology compared with the distilled water-treated control group. This study suggests that ascorbic acid supplementation may mitigate ciprofloxacin-induced reproductive dysfunction.